2023
DOI: 10.1101/2023.07.10.548341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of AI-Based Modeling on the Accuracy of Protein Assembly Prediction: Insights from CASP15

Abstract: In CASP15, 87 predictors submitted around 11,000 models on 41 assembly targets. The community demonstrated exceptional performance in overall fold and interface contact prediction, achieving an impressive success rate of 90% (compared to 31% in CASP14). This remarkable accomplishment is largely due to the incorporation of DeepMind's AF2-Multimer approach into custom-built prediction pipelines. To evaluate the added value of participating methods, we compared the community models to the baseline AF2-Multimer pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Another early study showed that a combination of AF2 predictions with the ClusPro docking protocol improved the success rate over using AF2 alone and confirmed that the quality of the resulting model was much higher than the usual docking model quality . A specific version of AF2, called AlphaFold-Multimer, was retrained on protein complexes and displayed improved performances for interface modeling over AF2, reaching a 67% success rate. ,, The potential of AlphaFold-Multimer has recently been confirmed in the CASP15 experiment . In parallel, RF was developed for the prediction not only of protein structures but also of protein complexes .…”
Section: Predicting Oligomeric Modelsmentioning
confidence: 92%
“…Another early study showed that a combination of AF2 predictions with the ClusPro docking protocol improved the success rate over using AF2 alone and confirmed that the quality of the resulting model was much higher than the usual docking model quality . A specific version of AF2, called AlphaFold-Multimer, was retrained on protein complexes and displayed improved performances for interface modeling over AF2, reaching a 67% success rate. ,, The potential of AlphaFold-Multimer has recently been confirmed in the CASP15 experiment . In parallel, RF was developed for the prediction not only of protein structures but also of protein complexes .…”
Section: Predicting Oligomeric Modelsmentioning
confidence: 92%